Defining the environmental performance of neighbourhoods in high-density cities. Issue 5 (4th July 2018) - Lau, Kevin Ka-Lun; Ng, Edward; Ren, Chao; Ho, Justin Ching-Kwan; Wan, Li; Shi, Yuan; Zheng, Yingsheng; Gong, Fangying; Cheng, Vicky; Yuan, Chao; Tan, Zheng; Wong, Kam Sing
ABSTRACT: The regenerative design framework aims to 'engage a broader range of possibilities by moving beyond the immediate building and site boundaries'. It implies that the environmental performance of buildings requires a revised definition so that it considers not only the building itself, but also its contribution beyond its own boundary, i.e. neighbourhoods. In high-density cities, outdoor spaces are culturally considered as the extension of one's living spaces. The environmental performance of neighbourhoods is particularly important to the health and wellbeing of urban inhabitants. This paper aims to define the environmental performance of neighbourhoods in high-density urban context based on the experience acquired in previous studies in Hong Kong over the last 15 years. These studies cover a wide range of environmental issues including urban climate, outdoor thermal comfort, and daylighting design in high-density cities. Subsequent development of the assessment tools for environmental performance of neighbourhoods in Hong Kong is also presented. The framework of stakeholder engagement, as an integral part of the neighbourhood assessment tool, is discussed. This paper highlights the distinctive features of the environmental performance of neighbourhoods in high-density urban context and how it influences the professional practices in Hong Kong.